2015
DOI: 10.1007/s00223-015-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Fat Infiltration in the Leg is Associated with Bone Geometry and Physical Function in Healthy Older Women

Abstract: The objective of this study was to estimate the associations between muscular fat infiltration, tibia bone mineral quantity and distribution, and physical function in healthy older women. Thirty-five women (aged 60-75 years, mean 70 years) were recruited from the community. Percent intramuscular fat (%IntraMF) within the right leg tibialis anterior, soleus, and gastrocnemius muscles and total intermuscular fat (IMF) were segmented from magnetic resonance imaging scans at the mid-calf. Intramyocellular lipid (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Lower gluteus maximus and abductor muscle densities are associated with lower hip areal bone mineral density (aBMD) in hip fracture patients (14), and measures of 'bone qualities', such as peripheral volumetric BMD (vBMD) and bone geometry (15), also appear to be poorer in those with lower muscle density. Indeed, we recently reported that lower mid-calf muscle density is associated with lower proximal tibial cortical vBMD and area in older adults (16), and high relative lower-leg intra-muscular fat has also been associated with lower tibial bone content and area (17). The findings of these studies suggest a potential negative localised effect of lower skeletal muscle density on bone health in older adults, but no study has reported associations between muscle density and bone density and architecture at multiple anatomical sites.…”
Section: Introductionmentioning
confidence: 92%
“…Lower gluteus maximus and abductor muscle densities are associated with lower hip areal bone mineral density (aBMD) in hip fracture patients (14), and measures of 'bone qualities', such as peripheral volumetric BMD (vBMD) and bone geometry (15), also appear to be poorer in those with lower muscle density. Indeed, we recently reported that lower mid-calf muscle density is associated with lower proximal tibial cortical vBMD and area in older adults (16), and high relative lower-leg intra-muscular fat has also been associated with lower tibial bone content and area (17). The findings of these studies suggest a potential negative localised effect of lower skeletal muscle density on bone health in older adults, but no study has reported associations between muscle density and bone density and architecture at multiple anatomical sites.…”
Section: Introductionmentioning
confidence: 92%
“…MRI was used to study intramuscular adipose tissue in frail and non-frail individuals, showing that more muscle fat infiltration was detectable in older frail subjects (18.0 vs. 11.7%) (51). In women over 50 years old, MRI-measured muscle fat infiltration was reported to be positively associated with increased fracture risk (52), while lower extremity muscle fat infiltration was shown to be negatively associated with performance based measures of physical function (53).…”
Section: Computed Tomography (Ct) and Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…This finding differs to in intact humans where the deterioration in muscle function occurs at ~2–3-fold greater rate than the loss of muscle mass (declines of ~2–3% vs. ~0.5–1.0% per year, respectively) [29, 30]. The reduction in muscle quality (i.e., strength per unit of muscle mass) with aging has been postulated to be occur due to changes in the muscle architecture [31], an increase in intermuscular fat infiltration [3234], greater muscle fibrosis [35, 36], and reduced neuromuscular activation [37, 38]. …”
Section: Determinants Of Muscle Strength and Function With Agingmentioning
confidence: 99%
“…However, results from our recent study, where increases in strength following omega-3 fatty acid supplementation were ~2-fold greater than the gain in muscle volume [78], provide at least some circumstantial evidence for an omega-3 fatty acid-induced improvement in muscle quality. Additionally, omega-3 fatty acid supplementation has been reported to improve neuromuscular function [85, 86] and reduce intermuscular fat infiltration [78], both of which help determine muscle quality and have been implicated in aging-induced declines in muscle function [37, 38, 3234]. Changes in other factors that influence muscle quality such as muscle architecture [31], and fibrosis [35, 36] have to the author’s knowledge not been examined in response to omega-3 fatty acids.…”
Section: Omega-3 Fatty Acid Intakementioning
confidence: 99%